Federal Housing Program - Techo Digno for the lower-middle class sectors: Implementation in Rosario, Santa Fe (ARQUISUR Revista, 2021)
During the last decades, urban development in our country was defined by the guidelines of the real estate market for social sectors that did not need financing. However, in 2009 certain housing policies aimed at low-income sectors that sought to create employment were extended to the middle sectors.In this context, the objective lies in the analysis of housing policy through the Federal Program for the Construction of Housing Roof Worthy given that it had its own characteristics in its implementation in the city of Rosario.The central points are linked to the description of the Program (objective, beneficiaries, lines of action), having previously exposed the Federal Program I and II, and with the scope of the four projects in Rosario (location, integration into the urban fabric, number of housing, prototypes).In short, in 2004, the State once again took center stage in housing policy with the Federal Program, including in 2009 the middle sectors with a Dignified Roof. However, there is access to the house and not to the city, the urbanizations located in the northwestern urban edge, where the infrastructures are expanded, but they lack complete services and equipment.
Keywords: access to the city, housing policy, Techo Digno Program, own housing, Rosario